2008
DOI: 10.1182/blood-2007-12-126938
|View full text |Cite
|
Sign up to set email alerts
|

Decreased differentiation of erythroid cells exacerbates ineffective erythropoiesis in β-thalassemia

Abstract: In ␤-thalassemia, the mechanism driving ineffective erythropoiesis (IE) is insufficiently understood. We analyzed mice affected by ␤-thalassemia and observed, unexpectedly, a relatively small increase in apoptosis of their erythroid cells compared with healthy mice. Therefore, we sought to determine whether IE could also be characterized by limited erythroid cell differentiation. In thalassemic mice, we observed that a greater than normal percentage of erythroid cells was in Sphase, exhibiting an erythroblast-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
181
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(194 citation statements)
references
References 59 publications
13
181
0
Order By: Relevance
“…In contrast, untreated Tg -/th3 mice increase 3 to 6 times ( Figure 8B) between fractions I and II as well as between II and III. This observation corroborates previous studies that indicate that β-thalassemic erythroid cells exhibit increased cell proliferation and reduced cell differentiation compared with those from normal mice (20). However, comparing the FACS profiles of WT and Tg -/th3 mice ( Figure 8, A and B, respectively) with those of Tg-Hamp/th3 mice ( Figure 8C), we observed that the latter group of mice exhibited an improved profile both in the spleen and BM (not shown), as indicated by a reduction in the number of cells in fractions II to IV, a more balanced ratio of the number of cells between these fractions and a relative increase in terminally differentiated cells in fraction V.…”
Section: Figuresupporting
confidence: 82%
“…In contrast, untreated Tg -/th3 mice increase 3 to 6 times ( Figure 8B) between fractions I and II as well as between II and III. This observation corroborates previous studies that indicate that β-thalassemic erythroid cells exhibit increased cell proliferation and reduced cell differentiation compared with those from normal mice (20). However, comparing the FACS profiles of WT and Tg -/th3 mice ( Figure 8, A and B, respectively) with those of Tg-Hamp/th3 mice ( Figure 8C), we observed that the latter group of mice exhibited an improved profile both in the spleen and BM (not shown), as indicated by a reduction in the number of cells in fractions II to IV, a more balanced ratio of the number of cells between these fractions and a relative increase in terminally differentiated cells in fraction V.…”
Section: Figuresupporting
confidence: 82%
“…[119][120][121] The Hbb th1/th1 mice were generated by a homozygous deletion of the b-major mouse globin gene, whereas Hbb th3/+ mice present a heterozygous deletion of both the b-major and b-minor globin genes in cis. [119][120][121] In these two models, the animals show a phenotype very similar to that observed in patients affected by NTDT, [122][123][124] such as splenomegaly and iron overload in absence of transfusion. An additional transplantable model showing features of b-thalassemia major has been generated by transplanting fetal liver cells from Hbb th3/th3 embryos into wild-type mice.…”
Section: Th3/+mentioning
confidence: 82%
“…33 In this regard; the condition of mk/mk mice treated with EPO resembles that of β-thalassemia mice with dramatically elevated endogenous EPO and increased BCL-X L expression, which is responsible for the prevention of apoptosis of thalassemic erythroid cells in this model. 19 The possible involvement of any substantial increase in iron utilization by individual erythroid cells as a contributing factor to the positive effects of EPO therapy can be ruled out by the fact that the patients' erythrocyte characteristics (MCV and MCH) remained unchanged with EPO supplementation. 7,32 Our observation of decreased MCV and MCH in the mk/mk mice following EPO treatment further supports this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…16 Ineffective erythropoiesis in different erythroid disorders is thought to be associated with increased apoptosis in the erythroid compartment. 17,18 Because a detailed study of β-thalassemia mice revealed only a low level of apoptosis, demonstrating that prevention of erythroid differentiation was causing ineffective erythropoiesis, 19 we set out to study the erythroid parameters that are rescued by a recombinant EPO in DMT1-mutant patients and mice.…”
Section: Introductionmentioning
confidence: 99%